Topological design and control of buck-boost multilevel inverters - Gao, Feng (2010)
Most dc-ac inverters developed to date can support only voltage buck energy conversion, and are therefore not suitable for use as interfacing inverters for tapping energy from renewable sources or other alternative clean sources like fuel cells, where an unrestrained voltage variation range is unavoidable. That obviously spells out the need to design inverters with both voltage buck and boost conversion abilities in order to gain maximum flexibility. Indeed, to cater for this rapidly growing interest in renewable / clean sources and other modem applications that require voltage buck-boost conversion, a number of buck-boost topological solutions have since been reported in the literatures with the most basic configuration being the series connection of a boost dc-dc converter at the front-end of a dc-ac voltage buck inverter. Although theoretically feasible, such a cascaded connection of two electronic converters is generally not attractive since it gives rise to a costly two-stage solution, which lacks optimization, and is also harder to control. Other solutions involving only a single-stage inverter have also been reported with most researchers trying to integrate semiconductor switches in a two-stage inverter to give a more compact single-stage topological alternative. Another possibility that has recently been reported is the integration of a Z-source LC impedance network between the dc input source and dc-ac inverter circuitry, where the complementary inductive and capacitive properties are known to give the Z-source inverter many advantages that are not exhibited by conventional inverters. Despite their effectiveness in performing voltage buck-boost conversion, nearly all the buck-boost inverters proposed to date are of the two-level type, meaning that their output pole voltages can switch only between two discrete voltage levels.